Matematyka
MarudnaB
5

Dam naj. za rozwiązanie wszystkich wyrażeń. Polecenie: Zapisz w prostszej postaci: 2a - 3a + 7 - 6 = 2x - 5x + 7 - x = 2a + b - 4b = x - 2x + 3 + x - 4 = 3x - y + 4x - 2y = 2x - 6 + 4x + 2 = 3y - 5 - 5y - 6 = -2a + 2b - 3a - 3b = ½t - 2x + 3t - x - t =

+0
(3) Odpowiedź
Joasia15

-a+1 -4x+7 2a-3b -1 7x-3y 6x-4 -2y-11 -5a-b 2.5t-3x

NeMiś

1.2a-3a+7-6=-a +1 2.=-4x+7 3.=2a-3b 4.=-1 5.=7x-3y 6.=6x-4 7.=-2y-11 8.=-5a-b 9.=2½t-3x

Busli1

2a - 3a +7 -6 = -a +1 2x - 5x + 7- x = -4x +7 2a + b - 4b= 2a - 3b x - 2x + 3 + x - 4 = -1 3x - y + 4x - 2y = 7x -3y 2x - 6 + 4x + 2 = 6x - 4 3y - 5 - 5y - 6 = -2y -11 -2a + 2b - 3a - 3b = -5a -b ½t - 2x + 3t - x - t = -3x + 2½t koniec :):)

Dodaj swoją odpowiedź